OVERPRODUCTION STRATEGIES FOR MICROBIAL SECONDARY METABOLITES: A REVIEW: Life Science-Molecular Biology - DAVATI, NAFISEH; B HABIBI NAJAFI, MOHAMMAD. (International Journal of Life Science and Pharma Research, 2013)
The formation of secondary metabolites is regulated by nutrients, growth rate, feedback control, enzyme inactivation, and enzyme induction. Regulation is influenced by unique low molecular mass compounds, transfer RNA, sigma factors and gene products formed during post-exponential development. The synthases of secondary metabolism are often coded by clustered genes on chromosomal DNA and infrequently on plasmid DNA. Strategies for overproduction of microbial products can be based on microbial response (Elicitors, quorum sensing), genetic engineering, metabolic engineering and ribosome engineering. Also molecular genetic improvement methods include amplification of SM biosynthetic genes, inactivation of competing pathways, disruption or amplification of regulatory genes, manipulation of secretory mechanisms, expression of a convenient heterologous protein, combinatorial biosynthesis.